2002
DOI: 10.1042/bst0300758
|View full text |Cite
|
Sign up to set email alerts
|

Novel cytotoxic chelators that bind iron(II) selectively over zinc(II) under aqueous aerobic conditions

Abstract: To achieve cellular iron deprivation by chelation, it is important to develop chelators with selective metal-binding properties. Selectivity for iron has long been the province of certain oxygen-donor chelators such as desferrioxamine, which target Fe(III) and exploit the strength of a relatively ionic Fe(III)-O interaction. We have been studying novel chelators that possess mechanisms to selectively chelate +2 biometals, particularly tachpyr [N,N',N"-tris(2-pyridylmethyl)-1,3,5-cis,cis-triaminocyclohexane] an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…8) is a hexadentate chelator based on a cis,cis-1,3,5-triaminocyclohexane scaffold that uses three pyridyl nitrogens and three secondary amine nitrogens to bind iron (for reviews, see Buss et al, 2003cBuss et al, , 2004a. Under aerobic conditions tachpyridine was found to bind Fe(II) more effectively than Fe(III) (Planalp et al, 2002). In addition, tachpyridine has been shown to bind Fe(III) and subsequently reduce it to the Fe(II) state .…”
Section: Kalinowski and Richardsonmentioning
confidence: 93%
“…8) is a hexadentate chelator based on a cis,cis-1,3,5-triaminocyclohexane scaffold that uses three pyridyl nitrogens and three secondary amine nitrogens to bind iron (for reviews, see Buss et al, 2003cBuss et al, , 2004a. Under aerobic conditions tachpyridine was found to bind Fe(II) more effectively than Fe(III) (Planalp et al, 2002). In addition, tachpyridine has been shown to bind Fe(III) and subsequently reduce it to the Fe(II) state .…”
Section: Kalinowski and Richardsonmentioning
confidence: 93%
“…In the presence of oxygen, Fetachpyridine is oxidized to its imino forms [157]. Although Zn 2+ bound tachpyridine more rapidly than Fe 2+ in vitro, Fe 2+ nearly completely displaced Zn 2+ from tachpyridine, indicating preference of tachpyridine for Fe 2+ [159]. Tachpyridine inhibits H 2 O 2 -induced DNA single-strand breaks in vitro, but has no effect on DNA damage caused by the combination of H 2 O 2 and superoxide ion [157].…”
Section: Tachpyridinementioning
confidence: 97%
“…Moreover, [Fe((N-Me) 3 tachpyr)] 2ϩ is a complex of high-spin (HS) Fe() that decomposes in anaerobic aqueous pH 7.4 media, whereas [Fe(tachpyr)] 2ϩ is indefinitely stable. 10 The findings indicated that the metal-binding properties of tachpyr are weakened by N-alkylation, likely from the steric effects of the introduced alkyl groups.…”
Section: Introductionmentioning
confidence: 99%